2016
DOI: 10.1021/jacs.6b06770
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic (Radio)Fluorination of α-Diazocarbonyl Compounds Enabled by Copper-Catalyzed H–F Insertion

Abstract: The copper-catalyzed H-F insertion into α-diazocarbonyl compounds is described using potassium fluoride (KF) and hexafluoroisopropanol. Access to complex α-fluorocarbonyl derivatives is achieved under mild conditions, and the method is readily adapted to radiofluorination with [(18)F]KF. This late-stage strategy provides an attractive route to (18)F-labeled biomolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
1
59
0
1
Order By: Relevance
“…In weiteren Kontrollexperimenten mit Rh II als Katalysator konnten die gewünschte Reaktion nicht beobachtet werden. Mit einem Kupferkatalysator und einem großen Überschuss HFIP wurden, neben erheblicher Nebenproduktbildung, geringe Mengen des Hexafluorisopropoxyethers 10 a erhalten, wie auch von der Doyle‐Gruppe beobachtet . Unter vergleichbaren Reaktionsbedingungen (1 Äq.…”
Section: Methodsunclassified
“…In weiteren Kontrollexperimenten mit Rh II als Katalysator konnten die gewünschte Reaktion nicht beobachtet werden. Mit einem Kupferkatalysator und einem großen Überschuss HFIP wurden, neben erheblicher Nebenproduktbildung, geringe Mengen des Hexafluorisopropoxyethers 10 a erhalten, wie auch von der Doyle‐Gruppe beobachtet . Unter vergleichbaren Reaktionsbedingungen (1 Äq.…”
Section: Methodsunclassified
“…[6][7][8] Ar ecent report on the fluorination of highly electrophilic copperc arbenesg enerated in situ provides an interesting foray in this direction (Scheme1). [9,10] Specifically,i tw as shown that a-diazoesters such as 1a,o nt reatment with catalytic amountso f[ Cu (MeCN) 4 ]PF 6 (or [Cu(OTf)] 2 ·PhMe) and L1 as the preferred ligand, react with excess KF in ab iphasic mixture comprised of hexafluoroisopropanol (HFIP) and 1,2-dichloroethane( DCE) at 40 8Ct og ive the corresponding a-fluoroester 2a in good yield. Despite the excellent track recordo fc hiral bis(oxazolines) (BOX) and related ligands in asymmetric catalysis, [11,12] however,o nly poor enantioselectivity ( 31 % ee)w as reached.U se of am onodentate chiral phosphoramidite in lieu of L1 entailedh ighero ptical purity (86 % ee)a tt he expense of the chemical yield, which dropped to only 12 %.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the excellent track recordo fc hiral bis(oxazolines) (BOX) and related ligands in asymmetric catalysis, [11,12] however,o nly poor enantioselectivity ( 31 % ee)w as reached.U se of am onodentate chiral phosphoramidite in lieu of L1 entailedh ighero ptical purity (86 % ee)a tt he expense of the chemical yield, which dropped to only 12 %. [9] uncatalyzed and hence racemic background reactionh ad to be prevented. [19] To this end, it was deemed imperative to find milder reactionc onditions and to carry out ab road ligand screening.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a H-bond network generated from HFIP could also act as a proton source in hydrofluorination (Scheme 1c), as shown by Doyle and coworkers in their copper-catalyzed H-F insertion into α-diazocarbonyl compounds using HFIP as proton source. [12] We are now glad to report the first 18 F addition protocol to an alkyne via a nucleophilic (radio)fluoro-click reaction, enabled by a hydrogen bonding cluster and using the readily available KF( 18 F) (Scheme 1d). …”
mentioning
confidence: 99%
“…[11] Because HFIP is as tronger Hbond donor than those alcohols,w ee xpected it to have an even stronger effect in the modulation of the nucleophilicity of fluoride.F inally,aH-bond network generated from HFIP could also act as ap roton source in hydrofluorination (Scheme 1c), as shown by Doyle and co-workers in their copper-catalyzed HÀFi nsertion into a-diazocarbonyl compounds with HFIP as the proton source. [12] We are now glad to report the first protocol for 18 Faddition to an alkyne through anucleophilic (radio)fluoroclick reaction, enabled by ahydrogen-bonding cluster and using readily available KF( 18 F) (Scheme 1d).…”
mentioning
confidence: 99%